Concepts of Takaful and its application in Takaful Ikhlas / Nur Insyirah Azmien - Azmien, Nur Insyirah (Academy of Contemporary Islamic Studies (ACIS), 2016)
The development of Malaysia’s economic currently shows its growth on Islamic muamalah system. This positive establishment gives one situation that attracts the society to analyze and choose between conventional and Islamic system. The economy system introduced Shariah rules that compiled all methods such as al-Bank alla Ribawi (banking without interest), al-Rahn (mortgage), Islamic business stock and of course Takaful (Islamic insurance). There are some methods and products like the al-Bank alla Ribawi and Takaful have been spread out to our neighborhood countries in example Brunei Darussalam, Indonesia and Singapore.